Assessment of Tear Osmolarity in Smokers Using TearLab and I-Pen Systems - Mana A. Alanazi; Gamal A. El-Hiti; Osamah A. Alturki; Muteb Alanazi; Raied Fagehi; Ali M. Masmali (Journal of Ophthalmology)
Purpose. Smoking has a negative effect on health and ocular tear film. The purpose of the current study is to investigate the correlation between the TearLab and I-Pen osmolarity scores in smokers and compare them with those of non-smoking healthy males. Methods. Thirty male smokers (25.3 ± 2.2 years) participated in the study. An age-matched (22.9 ± 2.0 years) control group of non-smoking healthy males (N = 30) was also recruited for comparison purposes. The ocular surface disease index (OSDI) was completed first, followed by the TearLab and I-Pen osmolarity measurements. Results. The median TearLab osmolarity score was lower (P < 0.001) than that obtained using the I-Pen in both the study and the control groups. The OSDI scores and osmolality measurements were higher (P < 0.001) in smokers than in the control subjects. In the smoker group, there were moderate correlations between the OSDI scores and the measurements obtained using the TearLab (Spearman’s correlation coefficient, r = 0.463; P = 0.010) and I-Pen (r = 0.449; P = 0.013) systems. In addition, there was a strong correlation between the osmolarity scores obtained from the TearLab and I-Pen systems in smokers (r = 0.911; P < 0.001). Conclusion. The I-Pen scores in smokers were significantly higher than those obtained using TearLab. The TearLab scores showed small variations compared with those obtained using I-Pen. A strong correlation was found between the TearLab and I-Pen scores in smokers. The osmolarity TearLab and I-Pen scores were significantly higher in smokers compared with normal eye subjects.